Curricular unit specification for programme assessment: fostering teacher reflection, while improving course catalogues - Barros, João Paulo (2014)
Reflective teaching is widely acknowledged as fundamental to improve practices leading to improved student learning. Presently, programmes are being assessed at several different levels, locally, or even countrywide. In this paper, we take as a starting point the template that all Portuguese higher education institutions have to fill for each curricular unit, for programme assessment purposes, and propose a more precise and informative format. Based on the literature, we argue this new template format fosters teacher reflection and provides additional and easier to compare data for accreditation boards, and the whole education community, most notably, students.